SYNTOPIC ELYMNIAS AGONDAS ARUANA FEMALE FORMS MIMIC DIFFERENT TAENARIS MODEL SPECIES (PAPILIONOIDEA: NYMPHALIDAE: SATYRINAE) ON ARU, INDONESIA - David J. Lohman; Sarino Sarino; Djunijanti Peggi (Treubia, 2020)
Wing patterns of female Elymnias agondas (Boisduval, 1832) butterflies are highly variable, presumably to mimic different Taenaris species throughout New Guinea and surrounding islands. Labels on most E. agondas museum specimens lack precise locality information, complicating efforts to match E. agondas female wing patterns with presumed Taenaris model species. This paucity of data also makes it impossible to determine where different forms occur and whether they are strictly allopatric. During fieldwork on the Aru Archipelago, we found two distinct forms of E. agondas females occurring syntopically. The “light form” resembles T. catops, while the “dark form” seems to mimic T. myops and T. artemis. We discuss the significance of this finding and illustrate species in the Taenaris mimicry ring encountered on Aru.